TRENDS OF ANTICOAGULANT PRESCRIPTION IN DIFFERENT HOSPITALS IN THE WEST BANK OF PALESTINE: A RETROSPECTIVE STUDY - Makhamra, Sajeda (An-Najah National University, 2024)
Background: Today, cardiovascular disease and thromboembolic events are the leading cause of death worldwide. Anticoagulants are increasingly popular in the prevention and treatment of thromboembolic events associated with atrial fibrillation, venous thromboembolism, deep vein thrombosis, and pulmonary embolism. In orthopedic departments, anticoagulants are frequently used in orthopedic surgery such as hip replacement and bone fracture as a prophylaxis from thromboembolism. In gynecology, anticoagulants are commonly used in pregnant women who have a high risk for thrombosis or have multiple miscarriages due to thrombosis. Objectives: This study was conducted to, evaluate trends in prescribing oral and parenteral anticoagulants in different Palestinian hospitals and visualize the increasing or decreasing trends in prescribing oral and parenteral anticoagulants in different Palestinian hospitals. Methodology: Prescription data of anticoagulants, including injectable and oral forms were retrospectively collected from Avicenna and dhis databases from 2019 -2023 in Hebron in the west bank. Comparisons were made on the use pattern of anticoagulants based on indications and years. Results: A total of 5121 patients were enrolled in the study. The mean age was (39.4 ± 18.0 years). The majority of patients were female (81.5%). There were increasing patterns in the total number of anticoagulant prescriptions. The prescriptions of novel oral anticoagulants (rivaroxaban, apixaban, and dabigatran) have significantly raised since 2020 with p-value <0.001 for rivaroxaban and apixaban, while the warfarin prescriptions have decreased. Rivaroxaban accounted for 63% of oral anticoagulants prescription followed by apixaban ( 26.6% ) and warfarin (8.8 %). Regarding injectable anticoagulants, heparin had constant use over the study period while enoxaparin prescription increased especially in the obstetric population. Enoxaparin use in the post-partum population increased from 11.2% in 2019 to 22.9% in 2023 and from 11% to 24.4% in pregnant women with thrombophilia mutations. Conclusion: Key findings indicate a significant rise in the prescription of novel oral anticoagulants, mostly due to their favorable pharmacokinetic and pharmacodynamic profile, the convenience of use, and less need for monitoring as compared to older therapies. As well as a notable rise in the prescription of enoxaparin in pregnant and postpartum women. With the potential to improve patient outcomes, the changing patterns in anticoagulant use are suggestive of a more significant shift in the treatment of thromboembolism disorder. Nevertheless, to maximize anticoagulant treatment for patients, continued investigations are required.
اتجاهات وصف الأدوية المضادة للتخثر في المستشفيات المختلفة في الضفة الغربية من فلسطين: دراسة بأثر رجعي